A novel non-enzymatic electrochemiluminescence sensor for the detection of glucose based on the competitive reaction between glucose and phenoxy dextran for concanavalin A binding sites. (20th October 2015) - Fan, Yu; Tan, Xingrong; Liu, Xiaofang; Ou, Xin; Chen, Shihong; Wei, Shaping
Abstract: A non-enzymatic electrochemiluminescence (ECL) sensor based on the competitive reaction between glucose and phenoxy dextran (DexP) for concanavalin A (ConA) binding sites was constructed for detecting glucose. The hybrid of graphitic carbon nitride nanosheet and 3, 4, 9, 10-perylenetetracarboxylic acid (g-C3 N4 -PTCA) as signal probe was modified onto the glass carbon electrode (GCE) for immobilizing DexP through π-π interaction. Then, ConA was incubated onto the electrode via the specific binding between ConA and DexP. When the modified electrode was immersed into glucose solution, glucose would compete with DexP for ConA. With the increase in the concentration of glucose, the more ConA was taken away from the electrode, resulting in a gradual increase in ECL intensity, thus, achieving the determination of glucose. The linear range was 1.0×10 −10 ∼5.2×10 −5  M and the detection limit was 4.0×10 −11  M (S/N = 3). Moreover, this sensor possessed high sensitivity, good stability and reproducibility, indicating a promising development of non-enzymatic ECL glucose sensor.